A Novel Iterative Velocity Control Algorithm and Its FPGA Implementation Based on Trigonometric Function. Issue 2 (1st March 2019) - Wen, Quangang; Liang, Yanchun; Adriano, Tavares; Ricardo, Teixeira; Wu, Chunguo
Abstract : The servo motor's flexible acceleration/deceleration (acc/dec) control is an emerging research topic in the automation field. A velocity control algorithm based on trigonometric function is proposed in this paper. With required parameters, it transforms trigonometric calculations into elementary mathematical operations and calculates the velocity controlling values iteratively, which could avoid trigonometric calculation and reduce the computation time. Experimental results show that the proposed algorithm is suitable for implementation on field programmable gate arrays and achieves a flexible controlling, enhancing both the equipment's stability and reliability. It is promising to significantly improve the high‐speed computerized numerical control equipment's controlling accuracy, without a huge hardware resource consumption.